Efeitos da adição in vitro de aminoácidos na qualidade seminal de asnos andaluzes após o descongelamento - Nogueira, Marina Bottrel Reis (2017)
The donkeys and their hybrids are versatile animals, rustic and totally adapted to the regions of arid climate. Although nationally the herd is large and expressive, there are scarce studies dedicated to the reproduction of this species. In Europe, advanced assisted reproduction techniques have been used as important tools in the conservation of endangered asinine breeds such as the Spanish Andalusian and Zamorano-Leonesa donkey breeds. The aim of this study was to evaluate the effect of amino acid (AA) addition to the freezing medium on post-thaw quality of donkey semen. In total, 18 ejaculates were collected from six Andalusian donkeys. Two donkeys were collected per day, the two collected semen samples were mixed in pools (2 ejaculates per pool), divided into ten aliquots, and cryopreserved in Gent A® containing 1% ethylene glycol (Gent-EG) supplemented with 0 (as control), 20, 40, or 60 mM for each glutamine, proline, or taurine. Fresh and frozen-thawed semen samples were assessed for sperm motility, morphology, acrosome integrity and plasma membrane integrity. The DNA fragmentation index (sDFI) was dynamically accessed in the thawed samples. The high concentration (60 mM) of the amino acids glutamine and taurine resulted in greater (P<0.001) post-thaw motility. The additives glutamine, proline and taurine did not improve (P>0.05) the mean ASM and MIS values compared with the control samples, while improvement (P<0.05) was observed at 60 mM for AIS when using glutamine. After thawing, there was no significant effect (P>0.05) in DNA preservation between treatments. However, at 6 h of incubation, the samples added 60 mM glutamine and 40 mM taurine presented lower sDFI (P <0.05) than the control samples. At 24 h, the sDFI values were lower (P<0.05) in all supplemented groups than in control extender, except only for 20 mM proline. In conclusion, the supplementation of the Gent-EG extender with glutamine or taurine at concentrations of 60 mM improved post-thaw donkey sperm quality.